2017
DOI: 10.1038/s41598-017-05388-9
|View full text |Cite
|
Sign up to set email alerts
|

A variation in PANK2 gene is causing Pantothenate kinase-associated Neurodegeneration in a family from Jammu and Kashmir – India

Abstract: Pantothenate kinase-associated neurodegeneration is a rare hereditary neurodegenerative disorder associated with nucleotide variation(s) in mitochondrial human Pantothenate kinase 2 (hPanK2) protein encoding PANK2 gene, and is characterized by symptoms of extra-pyramidal dysfunction and accumulation of non-heme iron predominantly in the basal ganglia of the brain. In this study, we describe a familial case of PKAN from the State of Jammu and Kashmir (J&K), India based on the clinical findings and genetic scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In an independent study using a PCR-based Direct Sanger Sequencing Strategy, our research group has identified an autosomal recessive variant NM_153638.3:c.1069C>T (NP_705902.2:p.Arg357Trp; rs753376100) located in exon 3 of PANK2 gene in a clinically suspected familial case of neurodegenerative disorder "Pantothenate Kinase-Associated Neurodegeneration" (PKAN; OMIM# 234000) (Angural et al, 2017). PKAN is a progressive neurodegenerative disorder characterized by an abnormal accumulation of iron in the basal ganglia in brain and extra-pyramidal manifestation (Hayflick et al, 2003).…”
Section: Rds-associated Genetic Studies Conducted In the Region So Farmentioning
confidence: 99%
See 1 more Smart Citation
“…In an independent study using a PCR-based Direct Sanger Sequencing Strategy, our research group has identified an autosomal recessive variant NM_153638.3:c.1069C>T (NP_705902.2:p.Arg357Trp; rs753376100) located in exon 3 of PANK2 gene in a clinically suspected familial case of neurodegenerative disorder "Pantothenate Kinase-Associated Neurodegeneration" (PKAN; OMIM# 234000) (Angural et al, 2017). PKAN is a progressive neurodegenerative disorder characterized by an abnormal accumulation of iron in the basal ganglia in brain and extra-pyramidal manifestation (Hayflick et al, 2003).…”
Section: Rds-associated Genetic Studies Conducted In the Region So Farmentioning
confidence: 99%
“…The variation identified is located at a highly conserved region in codon 357 of hPank2 protein and predicted to be pathogenic through in silico pathogenicity prediction tools. Through a comparative molecular dynamics study of the wild-type and variant hPank2 protein models, it was observed that the reported variation has rendered rigidity to the other highly dynamic protein structure which might have caused a functional compromise in hPank2 molecules (Angural et al, 2017).…”
Section: Rds-associated Genetic Studies Conducted In the Region So Farmentioning
confidence: 99%
“…A previous study has shown that the PANK family gene is associated with the prognosis of acute myeloid leukemia and pointed out that high expression of PANK2 may have a good effect on the prognosis of AML, while high expression of PANK4 indicates a poor prognosis [21]. Pantothenate kinase-related neurodegenerative disease is a rare hereditary neurodegenerative disease associated with nucleotide variations in the PANK2 gene encoded by mitochondrial human pantothenate kinase 2(PANK2) protein [22]. Pantothenate kinase-related neurodegenerative diseases are the main symptoms of pan-extrapyramidal dysfunction and non-heme iron accumulation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Pantothenate kinase-related neurodegenerative disease is a rare hereditary neurodegenerative disease associated with nucleotide variations in the PANK2 gene encoded by mitochondrial human pantothenate kinase 2(PANK2) protein [22]. Pantothenate kinase-related neurodegenerative diseases are the main symptoms of pan-extrapyramidal dysfunction and non-heme iron accumulation [22]. Although a few studies have suggested that PANK1 may play a key role in the occurrence of cancer [23], there is no literature exploring the correlation between PANK1 and renal clear cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The most common NBIA subtype, accounting for 35-50% of NBIA cases [2,3] is pantothenate kinase-associated neurodegeneration (PKAN) caused by biallelic variants in PANK2 (MIM #606157). PANK2 was the first causal gene discovered in NBIA, with cases reported from nearly all continents [1,[4][5][6][7][8].…”
mentioning
confidence: 99%